Association of amyloid-β CSF/PET discordance and tau load 5 years later - Reimand, Juhan (Neurology, 2020)
OBJECTIVE: To investigate the association between discordant β-amyloid (Aβ) PET and CSF biomarkers at baseline and the emergence of tau pathology 5 years later. METHODS: We included 730 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants without dementia (282 cognitively normal, 448 mild cognitive impairment) with baseline [(18)F]florbetapir PET and CSF Aβ(42) available. Aβ CSF/PET status was determined at baseline using established cutoffs. Longitudinal data were available for [(18)F]florbetapir (Aβ) PET (baseline to 4.3 ± 1.9 years), CSF (p)tau (baseline to 2.0 ± 0.1 years), cognition (baseline to 4.3 ± 2.0 years), and [(18)F]flortaucipir (tau) PET (measured 5.2 ± 1.2 years after baseline to 1.6 ± 0.7 years later). We used linear mixed modeling to study the association between Aβ CSF/PET status and tau pathology measured in CSF or using PET. We calculated the proportion of CSF+/PET− participants who during follow-up (1) progressed to Aβ CSF+/PET+ or (2) became tau-positive based on [(18)F]flortaucipir PET. RESULTS: Aβ CSF+/PET+ (n = 318) participants had elevated CSF (p)tau levels and worse cognitive performance at baseline, while CSF+/PET− (n = 80) participants were overall similar to the CSF−/PET− (N = 306) group. Five years after baseline, [(18)F]flortaucipir PET uptake in the CSF+/PET− group (1.20 ± 0.13) did not differ from CSF−/PET− (1.18 ± 0.08, p = 0.69), but was substantially lower than CSF+/PET+ (1.48 ± 0.44, p < 0.001). Of the CSF+/PET− participants, 21/64 (33%) progressed to Aβ CSF+/PET+, whereas only one (3%, difference p < 0.05) became tau-positive based on [(18)F]flortaucipir PET. CONCLUSIONS: Aβ load detectable by both CSF and PET seems to precede substantial tau deposition. Compared to participants with abnormal Aβ levels on both PET and CSF, the CSF+/PET− group has a distinctly better prognosis.